Tinjauan Yuridis Terhadap Kasus Perceraian Karena Masalah Ekonomi - Amelia Cahyani; Abdul Halim; Nurhaedah (Qawanin Jurnal Ilmu Hukum, 2020)
This study aims to determine and analyze the law of judges in accepting divorce cases for legal divorce for economic reasons in case Number: 514Pdt.G / 2020 / PA / Mrs. As well as to find out and analyze legal regulations related to divorce due to economic problems at the Maros IB Maros Religious Court.This research uses normative legal research methods, namely research that has the object of study of legal rules or regulations. The results of this study indicate that the Judge in deciding a divorce case due to economic factors is: divorce suit, which is based on the provisions of Article 49 paragraph (1) of Law Number 3 of 2006 concerning the first amendment to Law Number 7 of 1986 concerning the Religious Courts, including in the scope of absolute authority of the Religious Courts. Article 19 letter (f) of government regulation Number 9 of 1975 jo. Article 116 letter (b) Compilation of Islamic Law one party leaves the other party for 2 (2) consecutive years without the permission of the other party and without valid reasons or for other reasons beyond its capabilities and therefore economic problems occur because the Defendant (husband ) do not provide a living, Indeed in the divorce law because economic problems are not regulated in a limitative manner, However, divorce can be granted if the reasons are fulfilled as stipulated in KHI Article 116 letter (f) between husband and wife there are continuous disputes and quarrels and there is no hope of living in harmony again in the household. And most of the disputes and fights that occur in households are due to economic problems.The recommendation of this research is to complicate divorce procedures in order to reduce the rate of divorce that occurs by maximizing the role of the mediator and the Government should make a law on divorce because economic problems see divorce cases in Indonesia because there are quite a lot of economic problems. Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis hukum hakim dalam menerima perkara perceraian cerai gugat dengan alasan ekonomi pada perkara Nomor: 514Pdt.G/2020/PA/Mrs. Serta untuk mengetahui dan menganalisis peraturan hukum terkait perceraian karena masalah ekonomi di Pengadilan Agama Kelas IB Maros. Penelitian ini menggunakan metode penelitian hukum normatif, yaitu penelitian yang memiliki objek kajian tentang kaidah atau aturan hukum. Hasil penelitian ini menunjukkan Hakim dalam memutus perkara cerai gugat karena faktor ekonomi adalah : gugatan cerai, yang berdasarkan ketentuan Pasal 49 ayat (1) Undang-undang Nomor 3 Tahun 2006 tentang perubahan pertama Undang-undang Nomor 7 Tahun 1986 tentang Peradilan Agama, termasuk dalam lingkup kewenangan absolute Pengadilan Agama. Pasal 19 huruf (f) peraturan pemerintah Nomor 9 Tahun 1975 jo. Pasal 116 huruf (b) Kompilasi Hukum Islam salah satu pihak meninggalkan pihak lain selama 2 (2) tahun berturut-turut tanpa izin pihak lain dan tanpa alasan yang sah atau karena hal lain diluar kemampuannya dan oleh karena itu terjadilah masalah ekonomi karena Tergugat (suami) tidak memberikan nafkah, Memang dalam Undang-undang perceraian karena masalah ekonomi tidak diatur secara limitative, namun perceraian dapat dikabulkan apabila terpenuhi alasan sebagaimana diatur dalam KHI Pasal 116 huruf (f) antara suami istri terus menerus terjadi perselisihan dan pertengkaran dan tidak ada harapan akan hidup rukun lagi dalam rumah tangga. Dan kebanyakan perselisihan dan pertengkaran yang terjadi dalam rumah tangga yaitu karena masalah ekonomi. Rekomendasi penelitian ini yaitu dipersulitnya prosedur perceraian agar mengurangi tingkat perceraian yang terjadi dengan memaksimalkan peran mediator dan seharusnya Pemerintah membuat Undang-undang tentang perceraian karena masalah ekonomi melihat kasus perceraian di Indonesia karena masalah ekonomi lumayan banyak